Analytically based equations for distortion and residual stress estimations of thin butt-welded plates. (15th April 2017) - Hashemzadeh, M.; Garbatov, Y.; Guedes Soares, C.
Highlights: Analytical, finite element and experimental analyses of thin butt-welded plates are performed. Published empirical equations are revaluated and new relationships are proposed for design. Experimental test results and finite element analyses are used for equation validation. The relationships are in a good agreement with the collected experimental results and FE results. Different thicknesses of thin plates, weld sequences and weld shapes are tested. Abstract: Analytical, finite element and experimental analyses of thin butt-welded plates are performed for estimating thermal field, distortions and residual stresses. The existing empirical equations for the maximum distortion amplitudes are evaluated and new relationships are developed to estimate the distortion and residual stress spatial distributions on the thin butt-welded plates. To validate the newly developed equations, experimental test results and finite element analyses are used. The validation confirms that the developed relationships are in a good agreement with the collected experimental results and finite element analyses, representing common shipyard welding conditions. In addition, different thicknesses of thin plates are numerically investigated to validate the accuracy level of the new regression equations.